Self-poisoning with pesticides in Jiangsu Province, China: a cross-sectional study on 24,602 subjects - Wang, Boshen; Han, Lei; Wen, Jinbo; Zhang, Juan; Zhu, Baoli (BMC psychiatry, 2020)
With an estimated > 800,000 suicide-related deaths and potentially several attempts for each death in the world. The purpose of this study was to determine the epidemiological characteristics of self-poisoning with pesticides within the Jiangsu province in China. Suicide rate was calculated the Routine Surveillance System by Jiangsu Provincial Center for Disease Control and Prevention, stratified by gender, age and region, combined with socioeconomic and agriculture-related factors to investigate trends in suicide over the study period. A logistic regression model was used to investigate the associations between pesticide types and pesticide-related deaths. In recent years, Jiangsu Province has witnessed a decrease in pesticide self-poisoning cases and consequent deaths. Among all suicides by deliberate ingestion of pesticides, the proportion of cases were mainly in the age 40, accounting for 3.43% of all cases with pesticide suicide. The proportion of suicide due to pesticide poisoning in females was markedly higher than that in males (p < 0.001). Suicide using organophosphate and carbamate insecticides was most common, with 10,303 reported cases accounting for 42.02% of all suicides. For national responses to be effective, the characteristics of pesticide suicides should be comprehensively investigated for the formulation of corresponding prevention strategies. At present, more pesticide suicide prevention policies for the elderly people and women should be implemented, and stronger pesticide management policies should be implemented for rural areas.